The immune system - Parham, P. [ (Peter)] , 1950-; Janeway, Charles A. (Garland Science, 2015)
"The Immune System, Fourth Edition, emphasizes the human immune system and synthesizes immunological concepts into a coherent, up-to-date, and reader-friendly account of how the immune system works. Written for undergraduate, medical, veterinary, dental, and pharmacy students, it makes generous use of medical examples to illustrate points. The Fourth Edition has been extensively revised and updated. Innate immunity has undergone major revision to reflect this expanding and fast-moving field, and is now divided between two chapters: Chapter 2 "Innate Immunity: The Immediate Response to Infection," which deals with complement and other soluble molecules of innate immunity such as antimicrobial peptides, and Chapter 3 "Innate Immunity: The Induced Response to Infection," which deals mainly with the cellular response. Chapters 4-9 have been updated and material has been consolidated to eliminate repetition. Mucosal immunology has exploded as a field since the Third Edition was published, thus its coverage in chapter 10, now devoted to the topic, has been significantly expanded and updated. Also, more emphasis is placed on commensal microorganisms, particularly of the gut, and their interactions with the immune system. Immunological memory and the secondary immune response is now the first part of Chapter 11. The second part of this chapter, entitled "Vaccination to Prevent Infectious Disease," will include new and more modern material. "Bridging Innate and Adaptive Immunity" will also have its own chapter. The remaining clinical chapters will be revised and updated with new immunotherapies, but their content and organization will remain largely the same. The Fourth Edition will be accompanied by an updated and greatly expanded question bank, as well as PowerPoints and JPEGs of all the figures in the text."